Development of synthetic strategies towards multiporphyrin arrays - Ryan, Aoife (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
The aim of this research was to develop synthetic strategies for the construction of multiporphyrin arrays with enhanced π-conjugation. Porphyrin oligomers with extended conjugation display a bathochromic shift in their absorption profiles and thus have a diverse range of potential optical applications. As Prof Senge’s group has interest in the areas of photodynamic therapy (PDT) and non-linear optics (NLO), the design of such oligomers took these into account. One method to enhance the bathochromic shift is via the creation of conjugatively linked porphyrin oligomers. In our work, a series of symmetric and unsymmetric dimeric and trimeric porphyrin systems which are connected via conjugated linkers, namely alkyne and phenylacetylene, were synthesised via palladium catalysed C-C coupling reactions. These novel unsymmetric dimers and symmetric trimers were synthesised via the incorporation of all substituents on the monomeric components prior to coupling. The majority of these conjugated arrays exhibited a significant bathochromic shift in their UV/vis absorption profiles, in particular the alkyne linked arrays which showed absorption greater than 720 nm. The mass spectrometry spectra for phenylacetylene and diphenylbutadiene linked zinc arrays exhibited detachment of zinc from the porphyrin core in their spectra. These unusual results are both linker and metal dependent, usually only seen for more labile metals.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin